2018
DOI: 10.1016/j.tcm.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Thymidine phosphorylase: A potential new target for treating cardiovascular disease

Abstract: We recently found that thymidine phosphorylase (TYMP), also known as platelet-derived endothelial cell growth factor, plays an important role in platelet activation in vitro and thrombosis in vivo by participating in multiple signaling pathways. Platelets are a major source of TYMP. Since platelet-mediated clot formation is a key event in several fatal diseases, such as myocardial infarction, stroke and pulmonary embolism, understanding TYMP in depth may lead to uncovering novel mechanisms in the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 151 publications
(212 reference statements)
3
73
0
1
Order By: Relevance
“…Our results also revealed that ALDH6A1 is suppressed in ccRCC, which predicts poor prognosis. TYMP is a rate-limiting enzyme in the thymine catabolic pathway and contributes to tumor angiogenesis 26,27 . Prolyl 4-Hydroxylase Subunit Alpha 3 (P4HA3) is a critical enzyme in maintaining the stability of newly synthesized collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also revealed that ALDH6A1 is suppressed in ccRCC, which predicts poor prognosis. TYMP is a rate-limiting enzyme in the thymine catabolic pathway and contributes to tumor angiogenesis 26,27 . Prolyl 4-Hydroxylase Subunit Alpha 3 (P4HA3) is a critical enzyme in maintaining the stability of newly synthesized collagen.…”
Section: Discussionmentioning
confidence: 99%
“…MPO has been proven to play a key role in aggravating the inflammatory response and tissue damage in PV patients. In addition, TYMP has been demonstrated to directly stimulate the expression of angiogenic factors such as VEGF, TNFα, and IL-8 [18] as well as promote angiogenesis [19,20]. Moreover, IMPDH2, which is synthesized by guanine nucleotide rate-limiting enzymes, provides guanine nucleotides for T cell proliferation [21,22] and is highly expressed in proliferating tumor tissues [23].…”
Section: Discussionmentioning
confidence: 99%
“…MPO has been proven to play a key role in aggravating the in ammatory response and tissue damage in PV patients. In addition, TYMP has been demonstrated to directly stimulate the expression of angiogenic factors such as VEGF, TNFα, and IL-8 [18] as well as promote angiogenesis [19,20]. Moreover, IMPDH2, which is synthesized by guanine nucleotide rate-limiting enzymes, provides guanine nucleotides for T cell proliferation [21,22] and is highly expressed in proliferating tumor tissues [23].…”
Section: Discussionmentioning
confidence: 99%